2020
DOI: 10.1002/cjp2.193
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between immune checkpoint proteins, tumour microenvironment characteristics, and prognosis in primary operable colorectal cancer

Abstract: The tumour microenvironment is an important factor for colorectal cancer prognosis, affecting the patient's immune response. Immune checkpoints, which regulate the immune functions of lymphocytes, may provide prognostic power. This study aimed to investigate the prognostic value of the immune checkpoints TIM‐3, LAG‐3 and PD‐1 in patients with stage I–III colorectal cancer. Immunohistochemistry was employed to detect TIM‐3, LAG‐3, PD‐1 and PD‐L1 in 773 patients with stage I–III colorectal cancer. Immune checkpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
(56 reference statements)
1
21
1
Order By: Relevance
“…For example, one study reported that LAG-3 positivity on TILs in patients with NSCLC was predictive of shorter recurrence-free survival, [49] whereas another study found that LAG-3 on TILs in the intraepithelial and stromal parts of tumors and metastases predicted better disease-specific survival in 553 patients with stage I-IIIB NSCLC [106] . A study in 773 patients with stage I-III colorectal cancer found that high tumor expression of LAG-3 was related to a shorter survival, whereas high LAG-3 on immune cells in the stroma correlated with better survival [107] . Another study found that LAG-3 on TILs was a good prognostic factor in 89 patients who underwent resection for microsatellite instability-high colon cancers, [108] whereas LAG-3 +CD49b+ Tr1 cells were predictive of a poor prognosis and higher LAG-3 mRNA levels predicted advanced stages in colorectal cancer [109,110] .…”
Section: Correlation Between Lag-3 and Efficacy And Prognosis In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study reported that LAG-3 positivity on TILs in patients with NSCLC was predictive of shorter recurrence-free survival, [49] whereas another study found that LAG-3 on TILs in the intraepithelial and stromal parts of tumors and metastases predicted better disease-specific survival in 553 patients with stage I-IIIB NSCLC [106] . A study in 773 patients with stage I-III colorectal cancer found that high tumor expression of LAG-3 was related to a shorter survival, whereas high LAG-3 on immune cells in the stroma correlated with better survival [107] . Another study found that LAG-3 on TILs was a good prognostic factor in 89 patients who underwent resection for microsatellite instability-high colon cancers, [108] whereas LAG-3 +CD49b+ Tr1 cells were predictive of a poor prognosis and higher LAG-3 mRNA levels predicted advanced stages in colorectal cancer [109,110] .…”
Section: Correlation Between Lag-3 and Efficacy And Prognosis In Cancersmentioning
confidence: 99%
“…[ 106 ] A study in 773 patients with stage I-III colorectal cancer found that high tumor expression of LAG-3 was related to a shorter survival, whereas high LAG-3 on immune cells in the stroma correlated with better survival. [ 107 ] Another study found that LAG-3 on TILs was a good prognostic factor in 89 patients who underwent resection for microsatellite instability-high colon cancers, [ 108 ] whereas LAG-3 +CD49b+ Tr1 cells were predictive of a poor prognosis and higher LAG-3 mRNA levels predicted advanced stages in colorectal cancer. [ 109 , 110 ] An evaluation of the levels of expression of LAG-3 on stromal and intra-epithelial TILs (sTILs or iTILs) in breast cancers found that patients with LAG-3+iTILs had a better prognosis.…”
Section: Correlation Between Lag-3 and Efficacy And Prognosis In Cancersmentioning
confidence: 99%
“…A retrospective analysis was conducted to better identify the prognostic role of LAG3 [ 116 ]. In the 773 stages, I–III CRC patients underwent tumor resection surgery [ 106 ], and the expression of immune checkpoints at the stromal and tumor levels was evaluated by combining immune checkpoint stromal score (CICSS): CICSS 3 (TIM3- LAG3 and PD1 highly expressed), CICSS 2 (only two markers highly expressed), CICSS 1 (one high marker or weakly expressed markers).…”
Section: Long-standing and Emerging Immune Biomarkers In Crcmentioning
confidence: 99%
“…Quantitative analysis of immune checkpoints has been obtained by various methods and scoring systems. It is possible to use a weighted histoscore calculated as: (% unstained tumor cells × 0) + (% weakly stained tumor cells × 1) + (% moderately stained tumor cells × 2) + (% strongly stained tumor cells × 3) to give a range from 0 to 300 [ 116 ].…”
Section: Long-standing and Emerging Immune Biomarkers In Crcmentioning
confidence: 99%
“…Given the development of CRC therapy, there are now more choices for primary and metastatic patients; however, there are still some limitations. Increasing evidence has shown that the tumor microenvironment (TME) greatly influences the development of CRC ( 3 ) and that the TME plays an important role in tumor development. The coaction between tumor cells and their supporting cells and changes in metabolism and the immune environment have a close relationship with tumor growth and development ( 4 ).…”
Section: Introductionmentioning
confidence: 99%